The spread of the products and technology of metallurgy in the Carpathian Basin between 5000 and 3000 BC – Current questions - Siklósi, Zsuzsanna; Virág, Zsuzsanna M.; Mozgai, Viktória; Bajnóczi, Bernadett (Dissertationes Archaeologicae, 2018)
-